Temporary works principles of design and construction - Grant, Murray; Pallett, Peter F. (ICE, 2012)
The practicalities of temporary works are an essential, cost-and-safety-critical aspect of all construction projects, but receive minimum coverage in training and remain poorly understood by many engineers. Covering all sub-specialties of this wide-ranging topic in a single resource, this book is invaluable for permanent works designers, engineers, technicians and contractors looking to minimise costs, maximise efficiency and ensure the safety of those working on-site.